COST ANALYSIS OF HOME PHARMACY CARE PROGRAM AMONG DIABETES PATIENTS IN PHARMACY - Kiftiatin Nur Halisa; Didik Setiawan; Galar Sigit Prasuma (Universitas Airlangga, 2023)
Background: Home pharmacy care is expected to be able to provide a pharmaceutical service that not only reduces the incidence of drug interactions and side effects but also increases the effectiveness of therapy and patient compliance in using drugs. Aims: The study aimed to analyze the costs incurred for the home pharmacy care program for diabetic patients at the pharmacy. Methods: This analysis used the independent variable by providing a program of home pharmacy care. The dependent variable was the cost of running the program of home pharmacy care. The sample was the pharmacist in charge of the pharmacies in the Banyumas and Cilacap districts, which provide a home pharmacy care service program. The sample was conducted by purposive sampling method. Sampling was done by direct interviews with pharmacists who signed informed consent. Break Even Point (BEP) was calculated to determine the number of patients who must be served. The pharmacoeconomic analysis used is Cost Analysis using the activity-based costing (ABC) method. Results: The lowest rate for home pharmacy care services is Rp. 17,000, and the highest is Rp.31,000 without including home pharmacy care services. Conclusions: Pharmacies continue to benefit from the home pharmacy care program, and there is no provision for home pharmacy care service rates. Keywords:  Activity Based Costing (ABC), Diabetes Mellitus, Home pharmacy care (HPC)